2017
DOI: 10.12691/jpar-2-2-8
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Wrist-worn Heart Rate Monitors across a Range of Exercise Intensities

Abstract: Commercially available wrist-worn heart rate (HR) monitors have become increasingly popular.However, the accuracy of the devices across a range of exercise intensities is largely unknown. This study investigated the accuracy of four wrist-worn HR monitors (Apple Watch Series 1, Fitbit Charge, TomTom Touch, and Mio Fuse). Eighteen adults completed three trials on a cycle ergometer wearing a chest-worn HR monitor (Polar). Trial 1 established the HR-power output relationship, and resting and maximum HR. In trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…These results were similar to those of earlier studies that reported the high correlation between the heart rate measured by Fitbit and that measured by ECG, reference standard, in a laboratory environment composed of a treadmill and bicycle ergometer (Stahl et al, 2016;Hough et al, 2017;Gillinov et al, 2017;Shcherbina et al, 2017;Wang et al, 2017). Stahl et al (2016) reported that the heart rate measured by Fitbit Charge HR during walking and running on a treadmill showed the correlation of r=.93 with that measured in reference standard, and that the error rate between different intensities of exercises was within 1.73-10.06%.…”
Section: Accuracy Of Heart Rate Measuring Tool During Forest Exercisesupporting
confidence: 91%
See 3 more Smart Citations
“…These results were similar to those of earlier studies that reported the high correlation between the heart rate measured by Fitbit and that measured by ECG, reference standard, in a laboratory environment composed of a treadmill and bicycle ergometer (Stahl et al, 2016;Hough et al, 2017;Gillinov et al, 2017;Shcherbina et al, 2017;Wang et al, 2017). Stahl et al (2016) reported that the heart rate measured by Fitbit Charge HR during walking and running on a treadmill showed the correlation of r=.93 with that measured in reference standard, and that the error rate between different intensities of exercises was within 1.73-10.06%.…”
Section: Accuracy Of Heart Rate Measuring Tool During Forest Exercisesupporting
confidence: 91%
“…Meanwhile, it is essential to use wearable devices in order to monitor forest exercises in real time and provide feedback on whether the recommended intensity and amount of exercises are achieved. Currently, Polar, a device to measure heart rate wirelessly during forest exercises, is widely used (Choi et al, 2018;Choi et al, 2011;Shin et al, 2015;Lee et al, 2017), and it is known as a precise ECG device with very high accuracy (Engström et al, 2012;Gillinov et al, 2017;Hough et al, 2017;Wang et al, 2017). The amount of exercises, that is, energy consumption, during forest exercises have been hardly measured, but energy consumption during general exercises has been widely measured using Actograph's validated 3-axis accelerometer (Sasaki et al, 2011;Lee, 2012;Lee et al, 2014;Lee and Choi, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with ECG, PPG is easily accessible and low cost, which makes it an ideal intermedia of wearable heart rate measurement. Wrist-PPG has already been deployed in various commercial smartwatches or wristbands, such as Apple Watch, Fitbit Charge, and TomTom Touch, for heart-rate monitoring (Hough et al, 2017). The main disadvantage against ECG is that the PPG is relatively less informative and not unique for different persons and body positions.…”
Section: Photoplethysmography (Ppg)mentioning
confidence: 99%